Immunotherapy-Induced Sarcoid-Like Reaction: A Shrewd Imitator - Hassaan Yasin MD; Vivek Yadala MD; Noman Ahmed Jang Khan MD; Vincent Graffeo MD; Krista Denning MD; Yehuda Lebowicz MD (SAGE Publishing, 2021)
A 40-year-old male with a right-sided neck mass was diagnosed with metastatic melanoma. A repeat positron-emission tomography after treatment with combination immunotherapy demonstrated increased hypermetabolic activity in the right supraclavicular, hilar, and mediastinal regions. Immunotherapy was discontinued and a BRAF/MEK inhibitor combination was started. Repeat imaging showed a decrease in size of the neck mass; however, hilar and mediastinal lymph nodes increased in size. A fine needle aspiration of mediastinal lymph nodes was consistent with a granulomatous process. A diagnosis of a sarcoid-like reaction (SLR) was made, and he was started on steroids. A follow-up positron emission tomography showed decreased hilar and mediastinal lymph node hypermetabolic activity. We, therefore, report this rare case of immunotherapy-induced SLR to the expanding literature on immunotherapy-related adverse effects and would like to highlight that SLR can occur in conjunction with disease progression making it challenging to distinguish between the two.